Embedded 3D Printing of Thermally‐Cured Thermoset Elastomers and the Interdependence of Rheology and Machine Pathing. Issue 3 (30th October 2022) - Stang, Maria; Tashman, Joshua; Shiwarski, Daniel; Yang, Humphrey; Yao, Lining; Feinberg, Adam
Abstract: Thermoset elastomers are widely used high‐performance materials due to their thermal stability, chemical resistance, and mechanical properties. However, established casting and molding techniques limit the overall 3D complexity of parts that can be fabricated. Advanced manufacturing methods such as 3D printing have improved design flexibility and reduced development time but have proved challenging using thermally‐cured thermosets due to their viscosity, slow gelation kinetics, and high surface tension. To address this, freeform reversible embedding (FRE) 3D printing extrudes thermosets such as polydimethylsiloxane (PDMS) elastomer within a carbomer support bath, but due to the liquid‐like state of the prepolymer during extrusion has been limited to hollow structures. Here, FRE printing is significantly improved through rheological modification of PDMS with a thixotropic additive (1.0–10.0 wt.%) that imparts a yield stress (30–120 Pa) to help control filament morphology. Further, print process controls consisting of region‐specific slicing, filament retraction, and nonprint travel moves outside of the print to minimize the interaction of the nozzle with previously printed PDMS are implemented. The combined result is the FRE printing of PDMS in complex 3D parts with high fidelity, establishing a 3D printing methodology that can be used broadly with thermally‐cured thermoset elastomers and related polymers. Abstract : Freeform reversible embedding (FRE) 3D printing is combined with rheological modification and machine pathing to achieve high‐fidelity printing of thermally‐cured thermoset elastomers, using polydimethylsiloxane (PDMS) as a model material.